China's economic reform : a study with documents - Howe, Christopher; Kueh, Y. Y.; Ash, Robert F. (London : RoutledgeCurzon, 2002)
Publisher description: This book presents a collection and analysis of original policy documents, translated into English, from a key period of Chinese development, providing both a current and a retrospective analysis of China's economic reform efforts. Topics dealt with include the evolution of Chinese economic strategy; economic planning and the spread of market mechanisms; technology transfer in industry; evolution of an agricultural system; the development of population policy; and foreign economic relations. The collection will be of great interest not only to scholars and students of Chinese studies, but also to professionals and social scientists concerned with China but unable to read source documents in Chinese.
First issued in paperback 2011.
Includes bibliographical references (pages 399-404).
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: China -- Economic policy -- 1976-2000 -- Sources; China -- Economic policy -- 2000- -- Sources; Electronic books